WIND RELIABILITY ANALYSIS OF CABLE AND PYLON SURAMADU BRIDGE - MAJID EL YUMIN (NIM: 15011117), ABDURRAHIM
The basic structural form of a cable-stayed bridge consists of a number of triangles composed of the pylon, the stiffening girder, and the stay cables. Bridges mainly carry vertical loads and these are transferred locally by the stiffening girder to the elastic supports provided by the stay cables and subsequently through tension in the cables to the pylons. One of the common problems that are associated with a cable stayed bridge is the narrow dimension of the bridge which cause the bridge to be unstable towards the wind load. The wind load and traffic load cannot be determined easily because of the random distribution. So does the magnitude of the resistance of the structure because it depends on both the strength of steel and concrete. Thereby, there is a possibility of failing for the structure (specifically when the resistance is less than the load). Hence, there is a need to observe the reability of the cable structure in accordance to the dead load, the traffic load, and also the wind load. The wind disturbance on the structure also could cause a flutter and vortex shedding. There are also an evaluation of flutter and vortex shedding in this investigation. Based on the evaluation, it can be concluded that in term of its component, both cable‟s capacity and load are random variable which could be expressed with log normal distribution. Then, the bridge cable has a very small probability of structure failure towards the dead load, variation of the traffic load, and the wind load. Furthermore, based on the calculation of dynamical structure analysis for a period of 100 years, Suramadu Bridge is still safe against danger of flutter. However, there are indications that the vortex shedding islikely to occur.